Efficacy of bimatoprost for the treatment of primary open-angle glaucoma: A protocol of systematic review and meta-analysis. Issue 23 (5th June 2020) - Liu, Hong-wei; Lu, Yu-tong; Ren, Yong-bo; Meng, Yan
Abstract: Background: Bimatoprost has been reported to treat primary open-angle glaucoma (POAG) effectively. However, up-to-date, no systematic review has specifically addressed the efficacy and safety of bimatoprost for the treatment of POAG. Therefore, this study will propose to appraise the efficacy and safety of bimatoprost for the treatment of POAG. Methods: We will perform a systematic search in MEDLINE, EMBASE, CINAHI, Cumulative Index to Nursing and Allied Health Literature, Allied and Complementary Medicine Database, Web of Science, Cochrane Library, Chinese Biomedical Literature Database, and China National Knowledge Infrastructure from inception up to the March 1, 2020. We will include randomized controlled trials (RCTs) for evaluating the efficacy and safety of bimatoprost for the treatment of POAG. Primary outcome is the mean intraocular pressure (IOP) reduction from baseline to the endpoint, and change in best corrected visual acuity. Secondary outcomes are contrast sensitivity, rate of progression of glaucoma, quality of life, and incidence of adverse events. Study quality will be examined by Cochrane Collaboration tool, and strength of evidence will be evaluated by Grading of Recommendations Assessment Development and Evaluation tool. Results: This proposed study will outline the current RCTs to assess the efficacy and safety of bimatoprost for the treatment of POAG. Conclusion: The findings of this study will confirm whether bimatoprost is beneficial to patients with POAG. Systematic review registration: INPLASY202040118.